Producing the ecological economy: A study in developing fiduciary principles supporting the application of flow-fund consistent investment criteria for sovereign wealth funds (2019)
In the current financial climate, there is an opportunity for surplus capital to incentivize ecological economic production. Markets and financial products created in response to this surplus include investments in the maintenance of biologically viable natural systems and the development of sustainability transformation technologies. In this paper we critically examine their potential for supporting conservation and socio-ecological transformation. Using Nicholas Georgescu-Roegen's flow-fund theory, we take sovereign wealth fund (SWF) investments as a case in point and ask: according to what principles might it be possible to ensure that SWF investments are directed toward producing new economic processes compatible with the transformation to an ecological economy? Employing the flow-fund theory concepts of economic Anschauung and process-funds, we specify a flow-fund fiduciary responsibility associated with ensuring that an economic process is designed so that its final cause, or purpose, can be realized sustainably and sustained over time. We illustrate the generalizability of these fiduciary criteria by applying them to the two very different potential target investments: mangrove forest recuperation and conservation and the roll-out of the electric vehicle transport sector. We conclude with reflections on the general applicability of this approach and recommendations for further research. © 2019 Elsevier B.V.